Virtual Attractiveness of Quality Management Tools, Techniques and Methods - Piotr KAFEL; Paweł NOWICKI (Communications of International Proceedings, 2021)
Research background: Quality management is a wide topic that constitute a large number of tools, techniques or methods. This paper indicates the most popular ones, but focusing not on an organization or researchers perspective but rather on a perspective of anonymous internet user. This paper combines the specific quality management topics such as chosen tools, techniques or methods and its attractiveness calculated with the use of google trends search metrics. Purpose of the article: The purpose of the study was to determine which, well-known quality management tools, techniques and methods/principles within the world wide web users are the most attractive. Methods: The google trends tool was used to explore internet activity related to selected quality management tools techniques and methods/principles by users of all world countries. Findings & Value added: The main findings are related to the conclusion that the most attractive quality management tools, techniques and methods/principles within the world wide web users were: 5S, DOE, SPC, 5why and flowcharts. That tools and methods were more popular than well known methods such as ISO 9001 or Kaizen.
Keywords: Guality management tools; google trends; ISO 9001; lean management.